Los dos nacimientos de la fenomenología - Serrano de Haro, Agustín (2020)
The thesis of my essay is that it makes sense to affirm that phenomenology is born twice in Husserl's thought. Between the intentional psychology of Logical Investigations and the pure phenomenology of 1913 there is no coherent unfolding of a single philosophy that is gaining lucidity, as Husserl used to reconstruct his intellectual trajectory. But neither is there a theoretical discontinuity that would make transcendental phenomenology another philosophy, as the disciples of Göttingen or Heidegger himself tended to think: one that could have been born from other sources, influences or problems different from those of 1900-01. I therefore argue that the appearance of the world to life and of life to itself is the non-regional issue of phenomenological philosophy. Yet this problematic could only be reached descriptively by the lucidity of Logical Investigations in distinguishing between psychic experiences, ideal meanings and real objects, while at the same time the initial work was failing to find a link of regional ontology—¿psychic, logical, physical?—between these three dimensions of appearing.